Review of bioenergy initiatives in Indonesia for multiple benefits and sustainable development - Widayati, A.; Dermawan, A.; Solikhin, A.; Baral, H.; Bizarani, B.; Maulana, A.M.; Öborn, I. (Center for International Forestry Research, 2022)
Indonesia has committed to advancing its use of new and renewable energy (NRE) through its National Energy Policy (Kebijakan Energi Nasional). It has targeted NRE contributing 23% of the national energy mix by 2025, with bioenergy cited as one strategic measure for achieving this target. With Indonesia’s abundant biomass resources, it is worth assessing and exploring potential bioenergy feedstocks, and identifying opportunities and challenges for development and upscaling. With sustainability being on global and national agendas, Indonesia is no exception with its focus on bioenergy. This chapter discusses bioenergy development initiatives in Indonesia over the past 15 years through a review of literature from 2005–2018, and provides a general review and updates to 2020. It discusses emerging issues pertinent to multiple-benefit potentials, competing uses and other development agendas. The study looks at Indonesia’s abundant resources that could be developed for bioenergy, and discusses numerous studies dedicated to bioenergy development potential. Palm oil, Jatropha curcas and biogas are the most well-studied potential sources of bioenergy. Beyond these, implementation at scale remains a challenge, and feasibility studies including linkages with major offtakers are necessary. While many bioenergy initiatives have faced challenges with uptake, oil palm (Elaeis guinensis) biofuel is by far the most widely developed and used in Indonesia. Although opportunities exist to synergize bioenergy development with various development agendas, in some instances trade-offs might be necessary.